On the issue of numerical transformation of seismological signal - I. Yu. Mikhaylik; K. V. Petrenko (Геофизический журнал, 2012)
This article is devoted to conversion of seismic analog signal to digital code. The conversion is done by means of microprocessor instead of digital signal processor. This makes the data handling cheaper retaining its efficiency.